DEVELOPMENT OF SUSTAINABLE TOURISM INSTRUMENTS FOR ECOLOGICAL RESILIENCE IN PARI ISLAND, DKI JAKARTA - Samadi Samadi; Aris Munandar (GeoEco, 2024)
The research objective is to develop an instrument for assessing sustainable tourism in the context of ecological resilience in Pari Island, DKI Jakarta. This study uses research and development methods through the ADDIE model approach. The research sample includes potential and factual coral reef areas for tourism in Pari Island. The results of the study concluded that the validation of important instruments includes: (1) natural/biological criteria, namely unique and beautiful coral reefs, quite unique tidal phenomena, endemic flora and fauna such as seagrass and fish habitat, as well as other aquatic biota, ease of observing aquatic biota, opportunities for trekking, snorkeling, etc. as well as the support of comfortable temperature and humidity, normal rainfall conditions, as well as well-managed household industrial waste; and (2) Physical environmental criteria such as dominant beaches, controlled coastal land conversion rate and protected from pollution, ease of utilizing rocky beaches for friendly productive activities. The environment, such as maintaining fish, marine tourism, and others as well as the existence of a map of the distribution of coral reefs that accurately depicts local potential as well as information related to the low risk of natural disasters (landslides, floods, tsunamis).